Human capital from the viewpoint of creating company value. Challenges for financial controllers - Chalastra, Michał; Kotapski, Roman; Kozubíková, Zuzanna; Kozubík, Aleš (Kapitał ludzki z punktu widzenia tworzenia wartości dla przedsiębiorstwa. Wyzwania dla controllerów, 2019)
The research aim of this article is to look at human capital from the viewpoint of creating value for a company. In the era of the fourth industrial revolution (Industry 4.0), characterised by ever-increasing technological requirements, there is a demand for highlyqualified employees, including financial controllers, hence the key importance of their education and its scope. Knowledge limited to finance is not sufficient any more for future controllers since they will also have to have some orientation in the technology used by the company as well as its organization. As a result it will be necessary to implement a system of measuring the expenditure and the effects of creating intellectual capital in an enterprise. For these purposes it is possible to make use of the hard tools of controlling, such as budget, balanced chart of results, and the appropriate indicators for assessing this process
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 3, s. 3-9
Keywords: Industry 4.0; financial controller; przemysł 4.0; controller finansowy